Electrolyte and electrolyte-additives for improved plasma electrolytic oxidation on magnesium alloys - Viswanathan S. Saji (Applied Surface Science Advances)
Plasma electrolytic oxidation (PEO) is a pivotal method to create a thick and adherent protective oxide layer on magnesium (Mg) alloys, significantly enhancing their wear and corrosion resistance. The functional oxide layers fabricated via PEO have diverse potential applications, including automobile, aerospace, machinery, biomedical, thermal protection, catalysis, and energy materials. The type and nature of the electrolyte and electrolyte additives used in PEO play a decisive role in shaping the morphology, compactness, porosity, composition, thickness, wear/corrosion resistance, mechanical properties, and other functionalities of the resulting layer. The in-situ integration of chemicals/particles into the PEO layer, facilitated by optimized electrolyte additives, is a well-established method for producing enhanced composite oxide layers. This potential for creating enhanced composite PEO oxide layers is a promising aspect of PEO technology, and this review explores the latest strategies in optimizing electrolyte and electrolyte additives for superior PEO layers in various applications.